An analysis of the secondary school electricity curriculum via the taxonomy of introductory physics problems - Lazaar, Ahmed; Chafi, Chaimae; Riyahi, Jamila; Chergui, Mohamed (Intelektual Pustaka Media Utama, 2026)
One of the factors responsible for difficulties in learning electricity is the lack of relevance in the choice of cognitive activities engaged in teaching activities. Given this situation, we sought to explore cognitive aspects in the secondary school electricity curriculum and its implementation in textbooks. The study uses a mixed-methods approach to examine some cognitive aspects of the official framework texts and their implementation in the activities of final-year secondary school physical science textbooks. The corpus analyzed consists of 36 activities proposed in two officially accredited textbooks, totaling 258 questions covering the various topics in the electricity program. The taxonomy of introductory physics problems, designed for physics problems, is used as a data collection tool. The official texts and each question in textbooks activities are examined using a grid to identify the cognitive levels involved. After quantitative and qualitative data processing, the study revealed that all the cognitive levels of this taxonomy are recommended in the formal electricity curriculum, with a clear advantage for the two cognitive levels: comprehension and analysis. This choice of cognitive levels is relatively respected in the conceptualization activities proposed in the textbooks, with a strong preference for comprehension and analysis. The dependency between the cognitive levels involved in the activities and the topics on electricity has also been confirmed statistically. This dependence is justified by the fact that the degree of involvement of certain cognitive sub-levels of restitution and analysis varies significantly from chapter to chapter. We have also noted that the utilization of knowledge and certain sub-levels of analysis of knowledge are almost neglected.